2020
DOI: 10.1063/5.0012910
|View full text |Cite
|
Sign up to set email alerts
|

Infrared active surface modes found in thin films of perfluoroalkanes reveal the dipole–dipole interaction and surface morphology

Abstract: Infrared (IR) spectra of an organic thin film are mostly understood by considering the normal modes of a single molecule, if the dipole-dipole (D-D) interaction is ignorable in the film. When the molecules have a chemical group having a large permanent dipole moment such as the C= =O and C− −F groups, the D-D interaction induces vibrational couplings across the molecules, which produces an extra band as a surface phonon or polariton band because of the small thickness. Since the dipole moment of an organic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
(64 reference statements)
1
14
0
Order By: Relevance
“…Hasegawa and co-workers have demonstrated several pioneering research efforts for the evaluation of thin films with perfluoroalkyl chains. 50 In molecules having chemical bonding with large permanent dipoles such as C=O and C-F, vibrational couplings across the molecules are induced by dipole-dipole interaction, resulting in extra bands of surface phonon or polariton band. From the infrared spectral shape shifts upon a decrease in the thickness of the films, changes of molecular packings of perfluoroalkanes on a surface can be estimated with verification of stratified dipole-array theory for perfluoroalkyl compounds.…”
Section: •1 Recent Examples On Sensing and Analysis At Interfacesmentioning
confidence: 99%
“…Hasegawa and co-workers have demonstrated several pioneering research efforts for the evaluation of thin films with perfluoroalkyl chains. 50 In molecules having chemical bonding with large permanent dipoles such as C=O and C-F, vibrational couplings across the molecules are induced by dipole-dipole interaction, resulting in extra bands of surface phonon or polariton band. From the infrared spectral shape shifts upon a decrease in the thickness of the films, changes of molecular packings of perfluoroalkanes on a surface can be estimated with verification of stratified dipole-array theory for perfluoroalkyl compounds.…”
Section: •1 Recent Examples On Sensing and Analysis At Interfacesmentioning
confidence: 99%
“…The rocking bands were stronger in the case of (CF)10, which had a higher content of fluorinated groups. Moreover, the longer fluorinated chain in this sample caused a characteristic shift of the -CF 2 symmetric stretching vibrations' bands toward a higher wavenumber (from 1142 cm −1 as in (CF)6 to 1149 cm −1 ) [50]. Eventually, the spectrum of (CF)10 was distinguished by two strong bands related to the stretching vibrations observed at 1149 and 1204 cm −1 .…”
Section: Discussionmentioning
confidence: 78%
“…However, in the other two samples, when the number of fluorinated carbons in the alkyl chain increased, noticeable changes in the FTIR characteristics were observed. In comparison to (CF)0, the presence of the fluorinated groups can be confirmed by the following absorption bands located in the ranges: 520-730 cm −1 (bands assigned to the -CF 3 rocking and the -CF 2 wagging vibrations) and 1120-1250 cm −1 (the C-F stretching vibrations) [41,49,50]. The rocking bands were stronger in the case of (CF)10, which had a higher content of fluorinated groups.…”
Section: Discussionmentioning
confidence: 88%
“…Ovchinnikov and Wight also suggested that the line shape of the ν3 band depends on the macroscopic shape and orientation of the sample owing to the long-range nature of the dipole–dipole interactions. This implies that both the band shape and intensity can differ between the OP and IP spectra in IR-MAIRS, irrespective of molecular orientation. , We therefore speculate that some morphological changes occur in amorphous N 2 O as the film thickness increases during gas deposition over 1–128 min, leading to the change of the band shape and intensity of the OP spectra (Figure C,D). , …”
mentioning
confidence: 85%
“…43,47 We therefore speculate that some morphological changes occur in amorphous N 2 O as the film thickness increases during gas deposition over 1−128 min, leading to the change of the band shape and intensity of the OP spectra (Figure 2C,D). 29,48 In addition, the vibrational Stark effect can induce a frequency shift in the ν3 band of N 2 O, because an electric field can be applied across amorphous N 2 O film owing to anisotropic molecular orientation (dipole alignment). 22,25 The vibrational Stark effect on molecular-solid thin films at low temperatures has been studied for polycrystalline N 2 O.…”
mentioning
confidence: 99%